2018
DOI: 10.4236/psych.2018.92018
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Expert and Reflexive Approach to Problem-Solving: The Place of Emotional Knowledge and Skills

Abstract: Nowadays it is widely accepted that mathematics and, especially, problemsolving tasks, are particularly concerned by the issue of emotions. Yet, educational interventions designed to improve students' problem-solving competence and performance still mainly focus on cognitive and metacognitive knowledge and skills. The main purpose of this study was to design and assess the benefit of a training program that promotes the development of not only cognitive but also emotional knowledge and skills. This benefit was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 51 publications
0
8
0
1
Order By: Relevance
“…Although most research has also found that mathematics anxiety correlates negatively to perceived mathematics competence [34], there is little empirical research to date that has looked at the connection between upper elementary students' emotions and perceived competence in the mathematics context [35]. In this regard, we might assume perceived competence to negatively correlate with negative emotions and positively correlate with positive emotions [37].…”
Section: Perceived Competence Intrinsic Motivation and Academic Emotionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most research has also found that mathematics anxiety correlates negatively to perceived mathematics competence [34], there is little empirical research to date that has looked at the connection between upper elementary students' emotions and perceived competence in the mathematics context [35]. In this regard, we might assume perceived competence to negatively correlate with negative emotions and positively correlate with positive emotions [37].…”
Section: Perceived Competence Intrinsic Motivation and Academic Emotionsmentioning
confidence: 99%
“…Empirical evidence suggests emotions have deep, significant effects on learning and math achievement throughout students' educational careers (e.g., [33][34][35][36][37]). Considering that negative emotions experienced at early ages can affect an individual's construction of their academic identity [36], our study looks at the emotions in students in the final stages of primary education.…”
Section: Perceived Competence Intrinsic Motivation and Academic Emotionsmentioning
confidence: 99%
“…This information is critical for designing more effective training programs, as each strategy occupies a specific and central place in the problem-solving process. A study conducted with students of the same age emphasized that to increase more rapidly students' use of the "checking" and the "interpreting" strategies, it is necessary to add emotional and motivational support to the cognitive and metacognitive intervention (Hanin, & Van Nieuwenhoven, 2018b). This observation is in line with self-regulated learning theories, which postulate that motivational beliefs and emotions play a key role not only in initiating the learning process but also in sustaining the learner's efforts throughout the process (Boekaerts, 2011;Zimmerman, 2011).…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…Such a proposition is supported by research trends in education, psychology and neuroscience fields which show that aspects of cognition are bidirectionally influenced by aspects of emotions [50][51][52][53][54][55][56]. For example, problem-solving is found to be influenced by emotions [57] and motivation is linked to learning and academic performance [50,58]. While cognition and emotions affect learning and developing business competences [59], a sense of meaning and purpose is considered essential for successful business relationships and performance (spiritual knowledge) [60,61].…”
Section: Knowledge Dynamics Forms and Their Components In Be: A Frame...mentioning
confidence: 99%